Interleukin-10 Delays Viral Clearance in the Placenta and Uterus of Mice With Acute Lymphocytic Choriomeningitis Virus Infection During Pregnancy - Negi, Vidya Devi; Khurana, Sandhya; Bonney, Elizabeth A. (Frontiers in Virology, 2022)
Abstract Pregnant mice infected with Lymphocytic Choriomeningitis Virus (Armstrong) (LCMV-Arm) experience high viral loads in the placenta and uterine tissue by 5-8 days post-infection, a time when the virus is nearly completely cleared from the spleen and blood. Interleukin 10 (IL-10) plays a crucial role in T cell responses associated with systemic viral clearance. Using the LCMV-arm model of infection, we examined (1) whether IL-10 is involved in viral clearance in the placenta and uterine tissue and (2) the potential mechanisms underlying this phenomenon. C57BL/6 (WT) and mice deficient in IL-10 (IL-10 KO) were infected with LCMV-Arm on day 10 of pregnancy. Placenta and uterine tissue, collected 2 and 8 days later, were analyzed using real time RT-PCR, plaque assays for viral load, and flow cytometry. In WT mice placenta and uterine tissue expression of IL-10 was elevated with LCMV-Arm infection. Fetus resorption was elevated in WT on days 2 and 8 post-infection as compared to IL-10 KO, and by day 19 of gestation delivery was greater. Viral loads in the placenta and uterine tissue were resolved early in IL-10 KO mice, but persistent in tissues of WT mice. Levels of NRF2 and FAS were equivalent, but BCL2L11 was higher in IL-10 KO uterus. IL-6, Interferon-(IFN-), CCL2, and IL-17 levels were also equivalent. IL-10 KO tissues tended towards higher expression of interferon- (IFN-) and had significantly lower expression of Transforming growth factor beta (TGF-. The proportion of placenta and uterine tissue CD8 T cells expressing the activation markers CD44hi and PD1 were elevated in IL-10 KO mice. These data suggest that high IL-10 expression at the fetal-maternal interface following LCMV-Arm infection prevents clearance of viral load by impairing CD8 T cell activation and poses a significant threat to successful pregnancy outcome. The ability to modulate IL-10 expression at the maternal-fetal interface may help overcome negative pregnancy outcomes arising during acute LCMV and other viral infections in humans.